Effects of the exercise training on skeletal muscle oxygen consumption in heart failure patients with reduced ejection fraction. (15th November 2021) - Guimarães, Guilherme Veiga; Ribeiro, Fernando; Castro, Rafael Ertner; Roque, Jean Marcelo; Machado, Alexander Douglas Teixeira; Antunes-Correa, Ligia M.; Ferreira, Silvia Ayub; Bocchi, Edimar Alcides
Abstract: Aims: Skeletal muscle dysfunction is a systemic consequence of heart failure (HF) that correlates with functional capacity. However, the impairment within the skeletal muscle is not well established. We investigated the effect of exercise training on peripheral muscular performance and oxygenation in HF patients. Methods and results: HF patients with ejection fraction ≤40% were randomized 2:1 to exercise training or control for 12 weeks. Muscle tissue oxygen was measured noninvasively by near-infrared spectroscopy (NIRS) during rest and a symptom-limited cardiopulmonary exercise test (CPET) before and after intervention. Measurements included skeletal muscle oxygenated hemoglobin concentration, deoxygenated hemoglobin concentration, total hemoglobin concentration, VO2 peak, VE/VCO2 slope, and heart rate. Muscle sympathetic nerve activity by microneurography, and muscle blood flow by plethysmography were also assessed at rest pre and post 12 weeks. Twenty-four participants (47.5 ± 7.4 years, 58% men, 75% no ischemic) were allocated to exercise training (ET, n  = 16) or control (CG, n  = 8). At baseline, no differences between groups were found. Exercise improved VO2 peak, slope VE/VCO2, and heart rate. After the intervention, significant improvements at rest were seen in the ET group in muscle sympathetic nerve activity and muscle blood flow. Concomitantly, a significant decreased in Oxy-Hb (from 29.4 ± 20.4 to 15.7 ± 9.0 μmol, p  = 0.01), Deoxi-Hb (from 16.3 ± 8.2 to 12.2 ± 6.0 μmol, p  = 0.003) and HbT (from 45.7 ± 27.6 to 27.7 ± 13.4 μmol, p  = 0.008) was detected at peak exercise after training. No changes were observed in the control group. Conclusion: Exercise training improves skeletal muscle function and functional capacity in HF patients with reduced ejection fraction. This improvement was associated with increased oxygenation of the peripheral muscles, increased muscle blood flow, and decreased sympathetic nerve activity.